Genetic diversity of bottle gourd (Lagenaria siceraria (Molina) Standl.) landraces of South Africa assessed by morphological traits and simple sequence repeat markers. Issue 2 (2nd April 2016) - Mashilo, Jacob; Shimelis, Hussein; Odindo, Alfred
Abstract : Bottle gourd ( Lagenaria siceraria (Molina) Standl.) is an important crop in rural communities in South Africa but it remains under-researched. The objective of this study was to assess the genetic diversity present amongst bottle gourd landraces grown by smallholder farmers in South Africa using morphological traits and 11 selected polymorphic simple sequence repeat (SSR) markers. Marked phenotypic differences were observed amongst bottle gourd landraces. Principal component analysis on quantitative traits identified seven principal components, which accounted for 87% of the total variation. Number of alleles varied from 3 to 9 with a mean of 6 per SSR locus. Number of effective alleles ranged from 1.99 to 6.72 with a mean of 3.75. Shannon's information index varied from 0.95 to 2.01 with a mean of 1.41. Expected heterozygosity values ranged from 0.5 to 0.87 with a mean of 0.71 with polymorphic information content values of 0.5 to 0.85 and a mean of 0.7. Morphological traits and SSR marker analyses showed a significant correlation in clustering the landraces. The present study demonstrated the presence of genetic diversity amongst bottle gourd landrace collections from South Africa useful for strategic improvement, direct production or conservation.